2023
DOI: 10.18632/aging.205257
|View full text |Cite
|
Sign up to set email alerts
|

The ferroptosis landscape in acute myeloid leukemia

Zhixin Ma,
Wenle Ye,
Xin Huang
et al.

Abstract: Ferroptosis induction through the suppression of glutathione peroxidase 4 (GPX4) and apoptosis-inducing factor mitochondria-associated 2 (AIFM2) has proven to be an effective approach in eliminating chemotherapy-resistant cells of various types. However, a comprehensive understanding of the roles of GPX4 and AIFM2 in acute myeloid leukemia (AML) has not yet been achieved. Using cBioPortal, DepMap, GEPIA, Metascape, and ONCOMINE, we compared the transcriptional expression, survival data, gene mutation, methylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…It has been consistently reported that expression of GPX4 is elevated in most of AML cells and cell lines compared to their normal myeloid counterparts [ 35 ]. In this line, high expression of GPX4 in AML cells may also favor cellular growth and increase transformation potential.…”
Section: Gpx4 In Hematopoietic Stem Cells (Hscs) and The Myeloid Lineagementioning
confidence: 99%
See 1 more Smart Citation
“…It has been consistently reported that expression of GPX4 is elevated in most of AML cells and cell lines compared to their normal myeloid counterparts [ 35 ]. In this line, high expression of GPX4 in AML cells may also favor cellular growth and increase transformation potential.…”
Section: Gpx4 In Hematopoietic Stem Cells (Hscs) and The Myeloid Lineagementioning
confidence: 99%
“…Recently Ma et al, using multiparametric analysis of GPX4 and Apoptosis Inducing Factor Mitochondria Associated 2 (AIFM2) also called ferroptosis suppressor protein (FSP1) expression and function identified high expression of both proteins as novel biomarkers of pejorative prognosis in AML [ 35 ]. AIFM2 is a NAD(P)H-dependent oxidoreductase that catalyzes reduction of coenzyme Q/ubiquinone-10 to ubiquinol-10, a lipophilic antioxidant that prevents ferroptosis.…”
Section: Gpx4 In Hematopoietic Stem Cells (Hscs) and The Myeloid Lineagementioning
confidence: 99%